Design of a Service Plug-and-Play Middleware Based on SLP and mSLP - Zhang, Yu-Jun; Kung, Hsu-Yang; Tseng, Yu-Hua (IJRDO -Journal of Computer Science Engineering, 2017)
The middleware can provide the services for mobile computing assists user and service provider to transparently access heterogeneous services. This paper proposes a flexible Service Plug-and-Play Middleware based on mobile computing environment (SP2M). SP2M extends IETF Service Location Protocol (SLP) and Mesh-enhanced Service Location Protocol (mSLP) to provide scalable mobile services. This paper also proposes a novel Service Plug-and-Play (S-PnP) control procedure, which works as hardware Plug-and-Play service for legal users to provide flexible network application services over accessible heterogeneous service domains. The performance evaluation of the proposed S-PnP mechanism reveals that the scalability and successful rate of service discovery effectively are improved.